1987
DOI: 10.1002/j.1537-2197.1987.tb08675.x
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic Exudates From Velvetleaf (Abutilon Theophrasti) Glandular Trichomes

Abstract: Nonvolatile exudates from velvetleaf glandular trichomes inhibited root and shoot growth of several weed and crop species in petri plate bioassays, but had no effect on seed germination per se. The exudate was efficiently collected by wiping both the stems and petioles with cotton swabs or by leaching with water, but was absent on the leaves of velvetleaf plants. Cress (Lepidium sativum L.) was the most sensitive indicator species. Four types of trichomes appeared on the stem surface as revealed by scanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Looking at a different release mode, Sterling et al (1987) found that exudates from the glandular trichomes of velvetleaf were about twice as toxic when plants were grown under high-temperature stress, as compared with low temperatures. Water stress decreased the volume of trichome exudation, but the phytotoxicity of the exudate increased.…”
Section: Increases In Release Of Allelochernicalsmentioning
confidence: 99%
“…Looking at a different release mode, Sterling et al (1987) found that exudates from the glandular trichomes of velvetleaf were about twice as toxic when plants were grown under high-temperature stress, as compared with low temperatures. Water stress decreased the volume of trichome exudation, but the phytotoxicity of the exudate increased.…”
Section: Increases In Release Of Allelochernicalsmentioning
confidence: 99%
“…Artemisinin is highly phytotoxic to A. annua itself (Duke et al 1987), mak-ing sequestration within or secretion from the producing tissues a necessity. Autoallelopathic compounds of velvetleaf (Abutilon theophrasti), are found only in glandular trichomes (Sterling et al 1987). The subcuticular spaces of the glandular trichomes are likely sites of sequestration of artemisinin and other phytotoxic secondary compounds produced by A. annua.…”
Section: Introductionmentioning
confidence: 99%
“…Two types of non‐glandular trichomes (unbranched and stellate) and two types of secretory glandular trichomes (short and long) have been identified on the stem, petiole and leaf surface of A theophrasti . Secondary metabolites collected from the glandular trichomes of stems and petioles were shown to have allelopathic properties 21. In this study, examination was confined to the leaf surface where the short, capitate glands were found to contain magnesium and calcium.…”
Section: Discussionmentioning
confidence: 89%